Role of the cAMP-dependent carbon catabolite repression in capsular polysaccharide biosynthesis in Klebsiella pneumoniae. - Ching-Ting Lin; Yu-Ching Chen; Tzyy-Rong Jinn; Chien-Chen Wu; Yi-Ming Hong; Wen-Hao Wu (PLoS ONE, 2013)
K. pneumoniae is the predominant pathogen isolated from liver abscesses of diabetic patients in Asian countries. Although elevated blood glucose levels cause various immune problems, its effects on K. pneumoniae virulence are unknown. This study investigated the regulation of capsular polysaccharide (CPS) biosynthesis, a major determinant for K. pneumoniae virulence, in response to exogenous glucose. We found that K. pneumoniae produce more CPS in glucose-rich medium via reduction in cyclic AMP (cAMP) levels. Individual deletion of cyaA or crp, which respectively encode adenylate cyclase and cAMP receptor protein in K. pneumoniae, markedly increased CPS production, while deletion of cpdA, which encodes cAMP phosphodiesterase, decreased CPS production. These results indicate that K. pneumoniae CPS biosynthesis is controlled by the cAMP-dependent carbon catabolite repression (CCR). To investigate the underlying mechanism, quantitative real-time PCR and promoter-reporter assays were used to verify that the transcription of CPS biosynthesis genes, which are organized into 3 transcription units (orf1-2, orf3-15, and orf16-17), were activated by the deletion of crp. Sequence analysis revealed putative CRP binding sites located on P(orf3-15) and P(orf16-17), suggesting direct CRP-cAMP regulation on the promoters. These results were then confirmed by electrophoretic mobility shift assay. In addition, we found putative CRP binding sites located in the promoter region of rcsA, which encodes a cps transcriptional activator, demonstrating a direct repression of CRP-cAMP and P(rcsA). The deletion of rcsA in mutation of crp partially reduced CPS biosynthesis and the transcription of orf1-2 but not of orf3-15 or orf16-17. These results suggest that RcsA participates in the CRP-cAMP regulation of orf1-2 transcription and influences CPS biosynthesis. Finally, the effect of glucose and CCR proteins on CPS biosynthesis also reflects bacterial resistance to serum killing. We here provide evidence that K. pneumoniae increases CPS biosynthesis for successful infection in response to exogenous glucose via cAMP-dependent CCR.